2006
DOI: 10.1348/096317906x103997
|View full text |Cite
|
Sign up to set email alerts
|

Wider still and wider. Broadening the readership of the Journal of Occupational and Organizational Psychology

Abstract: Responding to my paper on how JOOP might widen its appeal to practitioners, Toby Wall, Gillian Symon and Gerard Hodgkinson broaden the debate, and offer further perspectives and suggestions. In reply, I argue that JOOP should continue to pursue this goal, and I counter Hodgkinson's view that JOOP's target readership should be limited to highly‐trained specialists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The March or June 2008 issue of JOOP will see a follow‐up to the lively debate on the scientist practitioner divide initiated by Garry Gelade last year (Gelade, 2006a, b) and joined by Toby Wall (2006), Gillian Symon (2006), Gerard Hodgkinson (2006), and Neil Anderson (2007). As indicated in my previous editorial (Arnold, 2007), JOOP will periodically publish invited papers on how recent JOOP output looks from a practitioner perspective ‐ with the author given free rein to say what he or she likes.…”
Section: Some Previews Of Joop In 2008 and Beyondmentioning
confidence: 99%
“…The March or June 2008 issue of JOOP will see a follow‐up to the lively debate on the scientist practitioner divide initiated by Garry Gelade last year (Gelade, 2006a, b) and joined by Toby Wall (2006), Gillian Symon (2006), Gerard Hodgkinson (2006), and Neil Anderson (2007). As indicated in my previous editorial (Arnold, 2007), JOOP will periodically publish invited papers on how recent JOOP output looks from a practitioner perspective ‐ with the author given free rein to say what he or she likes.…”
Section: Some Previews Of Joop In 2008 and Beyondmentioning
confidence: 99%
“…He concluded that in some respects JOOP 's content is more relevant to practitioners than he at first anticipated, but that nevertheless, there were a number of ways in which JOOP could become more practitioner‐friendly. Commentaries from Wall (2006), Symon (2006), Hodgkinson, 2006) and Anderson (in press), and Gelade's response to the first three (Gelade, 2006b), have thrown up further practical suggestions. Stimulated by these debates, and building upon Arnold (2004), the position taken by JOOP is:…”
Section: Science and Practicementioning
confidence: 99%
“…The following developments to JOOP 's editorial procedures are being made in order to improve communication between research and practice. As Gelade (2006a,b) and Van de Ven and Johnson (2006) have pointed out, the effectiveness of measures like these depend upon several factors. Probably the two most important are (i) the assumption that a large part of the problem of poor links between research and practice lies in poor communication of the research, rather than the research being irrelevant to practice in the first place and (ii) that the people involved will be willing and able to make the effort to improve communication.…”
Section: Science and Practicementioning
confidence: 99%
See 2 more Smart Citations